Optimization of Police Authority as Gatekeepers in the Prevention and Eradication of Gambling Crimes - Verdy Hengky Kalele; Evita Isretno Israhadi (Journal of World Science, 2024)
This study explores the optimization of police authority as gatekeepers in preventing and eradicating gambling crimes in Indonesia. Using a normative legal research method, it examines legal frameworks, administrative challenges, and social dynamics affecting law enforcement efforts. A legislative approach reviews relevant legal provisions, while a conceptual approach analyzes the police's role in crime prevention. Findings reveal that limited resources, insufficient community cooperation, rapid technological advancements in online gambling, and complex legal constraints hinder police effectiveness. Key recommendations include enhancing community partnerships, conducting regular police training, fostering inter-agency collaboration, and leveraging information technology to strengthen law enforcement capacity. These measures aim to improve crime prevention and eradication strategies while fostering public trust and promoting legal compliance. The proposed reforms offer a roadmap for developing more effective policing strategies and creating safer communities through proactive and responsive law enforcement practices.